Determinants of the Level of Government Financial Independence in Districts/Cities in South Sumatera - Maria Maria; Khoiria Afriana; Bainil Yulina (Jurnal Akuntansi dan Keuangan, 2025)
Based on data from LKPD of districts/cities in South Sumatra over the last 10 years, the mean level of financial independence in the region is around 11%, with significant disparities between regions. Palembang City has the highest level of independence at 49%, while most other regions have levels below 12%. These findings indicate that subnational financial independence is affected by various determinants. To analyze this, the study applies a fixed-effect panel data regression model using EViews version 13. The research demonstrates that the size of subnational government has a positive and significant influence. In contrast, Leverage and subnational incentive funds have no significant effect. Capital expenditure exerts a negative and significant influence. Simultaneously, the analysis reveals that the four variables exert a significant effect on subnational financial independence. This finding indicates that any policy on government activities significantly impacts the financial independence of the government.